The Impact of Drill Training on the Serviceability of the Sepak Takraw Team in Louk Village - Ardiansyah Nur; Abu Bakar; Ahmad Syarif Burhan; Ady Prasetya A. Ayuba (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. This investigation aims to collect information regarding the potential impact of drill training on the serviceability and performance of the Sepak Takraw team from Louk Village. Materials and methods. The methodology employed is experimental research utilizing a one-group pretest-posttest design, which implies the absence of a control group. Results. The data analysis indicates that the paired sample t-test calculation yields a t-count value of 13.077 and a t-table value of 2.262, with a significance level 0.000. The degree of freedom (df) is 9 and the p-value, with a significance level (α) of 0.05, is 0.050. Since the calculated t-value (t-count) of 13.077 is more than the critical t-value (t-table) of 2.262 at a significance level of 0.05, we reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha). Conclusion. Therefore, it can be inferred that drill training has a substantial impact on the performance capabilities of the Louk village Sepak Takraw squad.